PENGARUH MOTIVASI TERHADAP PRODUKTIVITAS PEGAWAI PADA PUSKESMAS GEDONGPANJANG KOTAISUKABUMI - Ike Rachmawati (Mimbar Administrasi Mandiri, 2023)
The mainiproblem of this study is the low work productivity of employees, which based on the results of the pre-survey of researchers, is caused by the perceived motivation and quality of service that is not optimal. Based on these main ideas and considerations, the researcher intends to examine further. The approach method used in this study is a quantitative method using a questionnaire instrument. The results of the study show that there is a positive and significant influence on the use of motivation on the quality of service in the Gedong Panjang Health Center, Sukabumi City, with the magnitude of the influence of Adjusted R2 = 0.920 or the magnitude of the influence of the use of motivation on service quality of 92.0%, and makes a significant contribution significant.